Mineração em Geossistemas Ferruginosos e Questões de Geoética: o Caso do Rompimento da Barragem de Córrego do Feijão, Minas Gerais – Brasil - Úrsula de Azevedo Ruchkys; Paulo de Tarso Amorim Castro; Marcos Paulo Souza Miranda (Confins)
The State of Minas Gerais, southeast portion of Brazil, is one of the largest miners in the country. In the Quadrilátero Ferrífero region are located the main regional iron and gold mines. In the last three years, two major crimes occurred due to the rupture of iron mine tailings dams: Fundão (2015) and Córrego do Feijão (2019). This article aims to analyze the break of the tailings dam of Córrego do Feijão, from Vale Mining Company, from the perspective of geoethics, having as source of information two important Brazilian newspapers. In order to do so, it presents a relation between geoethics and the breakdown by analyzing the Vale mining company's information in these newspapers regarding the leakage of tailings and its consequences considering environmental and social effects, communication, to provide for the remediation of any potential hazards and concern and responsibility to future generations. The analyzes carried out indicate the need for a geoethics approach in the design and implementation of mining activities.